Fundamental solutions of boundary problems and resolvents of differential operators - Mogilevskii, V. (Український математичний вісник, 2009)
The main objects of our considerations are differential operators generated by a formally selfadjoint differential expression of an even order. The coefficients of this expression are operator valued functions defined on the interval [0, bi (b ≤ ∞) with values in the set of all linear bounded operators in a separable Hilbert space H. Our approach is based on the concept of a decomposing D-boundary triplet, which enables to describe various properties of (regular and singular) differential operators immediately in terms of boundary conditions.